Automatic vehicle detection system - Syahrul Nizam, Zaini (2007)
This project is based on webcam, Graphical User Interface (GUI), the relationship of each part for image processing and server client connection. This system is designed to automatically & remotely determine whether parking is empty or full. The monitoring system is written using Microsoft Visual Basic Version 6 language. Edge detection is used to image reduces significantly the amount of data and filters out information that may be regarded as less relevant, preserving the important structural properties of an image. The captured image that will be compared to the default image to see the outcome if image either full or empty. This is one of image processing part that called differences. This concept cans different two images and then analysis it using Correlation coefficient concept. The data will be updated on the server that sends information on the availability of a parking space to client using internet connection. The data will be updated based on feedback of output parking system or if a client asked for the information.